Active methodologies as an instrument for a sensitive look and cozy about the importance of vaccination in adolescents (Research, Society and Development, 2020)
Objective of this study is to describe the experience of nursing professionals on the subject of immunization with students from a public school in the city of Teresina. This is a descriptive study based on an experience report by resident nurses from the Multiprofessional Residency Program in Family and Community Health in partnership with the Expanded Family Health Center and representatives of the Family Health Strategy team in a municipal public school located in the south of Teresina-PI. The health education action was constituted in three different moments, being these: Welcoming, executed through a dynamic "ice breaker", which aimed to begin the construction of links between professionals and students, development, in which it was possible to perceive the previous knowledge of the students on the subject, through the distribution of cards, followed by the joint construction of a conceptual map elaborated with the knowledge passed on by the resident nurses, decreasing doubts and presenting a new perspective on the importance of immunization, and finalization, through the dynamics of myths and truths. It is concluded that although the students have general knowledge about immunization, some information is passed on to them incompletely, and it is necessary to develop actions that promote students awareness of immunization practices. It is important to emphasize the importance of health professionals to take advantage of active methodologies, acquiring a more sensitive, culminating in greater assimilation of knowledge by the participants and sharing of knowledge.